Effect of legume persistence in endophyte-infected tall fescue pastures on forage production and steer performance - Lomas, Lyle W.; Moyer, Joseph L.; Kilgore, Gary L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 135 steers grazed high-endophyte tall fescue pasture in 1998, 1999, and 2000 that had been previously interseeded with either lespedeza, red clover, or ladino clover during 1995, 1996, and 1997. Legume cover, forage dry matter production, grazing steer performance, and subsequent feedlot performance were measured. Pastures interseeded with ladino clover produced higher stocker gains in 1998 and more available forage and legume cover in all 3 years than those interseeded with lespedeza or red clover. Legume treatment had little effect on subsequent finishing performance. Results of this study indicate that lespedeza and red clover should be seeded every year and ladino clover at least every 2 years in endophyte-infected tall fescue pasture in order to provide sufficient legume to improve performance of grazing cattle.
Keywords: Beef; Grazing; Tall fescue; Endophyte; Legumes; Interseeding; Finishing